The Effect of Using Pop-Up Book Learning Media on Speaking Skills of Grade IV Students in the Indonesian Language Subject - Ihsani, Suciati Tri; Simbolon , Marlina Eliyanti; Prasetio, Pajar Anugrah (Universitas Nusantara PGRI Kediri, 2025)
The study was conducted to describe the differences in speaking skills of students who use Pop-Up Book learning media with students who use Talking Stick learning media and to describe the differences in improving speaking skills of students who use Pop-Up Book learning media with students who use Talking Stick learning media in the Indonesian Language subject for grade IV. This study was conducted at SD Negeri 1 Winduhaji, Kuningan District, Kuningan Regency using a quasi-experimental research method. The design of this study was a nonequivalent control group design. The subjects of this study were grade IV of SD Negeri 1 Winduhaji which had two classes, namely class IV A (experimental class) consisting of 25 students and class IV B (control class) consisting of 24 students. The data analysis technique used was quantitative analysis obtained from the pretest and posttest results. The data analysis was analyzed using a t-test, from the results of the analysis showed that the two classes had differences in speaking skills and differences in improving speaking skills between students who used Pop-Up Book learning media and students who used Talking Stick learning media. So it can be explained that there is an influence of Pop-Up Book learning media on students' speaking skills.